The second front. (Economist, 1998)
Reports on the decision of a federal judge in San Jose, California to order Microsoft Corp. to stop shipping its own version of Java, an Internet software language created by Sun Microsystems. The impact that the decision could have; Description of the agreement between Sun and Microsoft over the usage of Java; Sun's decision to sue Microsoft; The psychological damage of the decision on Microsoft.